FEATURES OF THE SECONDARY RESTRICTION PROCESS - Abdirazakov Akmal Ibrahimovich; Axmedov Muxtor Muzaffarovich; Do'stmurodov Abdumannon Norqobilov o'g'li (Scholar Express Journals, 2024)
This article provides information about the features and requirements of secondary drilling of a productive formation, types of perforations used during secondary drilling, and their disadvantages
Keywords: Wells; Perforation; Formation